Sow thistle (sonchus oleraceus l) plants growth and chemical composition from the aboveground part in Kazakistan - Amangeldi, N.; Amangeldikyzy, Z.; Abdukerim, R. Zh.; Yerezhepova, A. (Ғылым және білім=Наука и образование=Science and education. - 2024. - № 3-2 (76). Ч. ІІ. - Р. 28-38, 2024)
Kazakhstan's plenty of geographic climates offer an ideal environment for the development and research of thistle medicinal plant species, which are abundant in bioactive chemicals. The identification and measurement of important substances such as amino acids, fatty acids, and vitamins were highlighted in this study, which focuses on the chemical composition of the Sow thistle (Sonchus Oleraceus L.) plant in Kazakhstan. Medicinal plants, as is well-known, have long been acknowledged for their therapeutic features, providing a natural substitute for manufactured medications that may have less negative effects. Utilizing advanced physicochemical methodologies and chromatographic techniques, the study effort aims to clarify the possible medicinal uses of this particular plant species. The State Pharmacopoeia of the USSR and previous phytochemical studies established methodologies, standards and underscored the rigor and reliability of the analytical approach. The findings of this study contribute to the growing body of knowledge on the bioactive constituents of Sow thistle medicinal plants in Kazakistan, highlighting their pharmacological significance and potential for drug discovery. By harnessing the chemical diversity of Kazakhstan's flora, researchers can unlock new opportunities for the development of pharmaceuticals, nutraceuticals, and other health-promoting products derived from natural sources.
Keywords: РК; журнал кокснво; sow thistle (sonchus oleraceus l); chromatogram; surfactant; spectrophotometry; лекарственные растения; осот